2006
DOI: 10.1007/s11524-006-9047-4
|View full text |Cite
|
Sign up to set email alerts
|

Community Reentry: Perceptions of People with Substance Use Problems Returning Home from New York City Jails

Abstract: Each year about 100,000 people return to New York City communities from municipal jails. Although about four-fifths report drug or alcohol problems, few have received any formal drug treatment while in jail. Researchers and practitioners have identified a number of policies related to corrections, income, housing, and drug treatment that may be harmful to the successful reintegration of people leaving jail. In order to explore the challenges to successful community reentry, six focus groups and one in-depth in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 9 publications
1
52
0
1
Order By: Relevance
“…Ex-offenders who used drugs before or during incarceration face strong temptations to return to drug use, caused in part by addiction and having little else do as jobs are harder to obtain with a prison record. 25 This study in one county of NC has strengthened arguments for a connection between incarceration and STIs that was first inferred from county-level comparisons in NC. The magnitudes of the effects at the census-tract-level were consistent with those seen at the county-level.…”
Section: Discussionsupporting
confidence: 55%
“…Ex-offenders who used drugs before or during incarceration face strong temptations to return to drug use, caused in part by addiction and having little else do as jobs are harder to obtain with a prison record. 25 This study in one county of NC has strengthened arguments for a connection between incarceration and STIs that was first inferred from county-level comparisons in NC. The magnitudes of the effects at the census-tract-level were consistent with those seen at the county-level.…”
Section: Discussionsupporting
confidence: 55%
“…[64][65][66][67][68] In a qualitative study with a population recently released from jail in this issue of the Journal of Urban Health, participants noted financial, structural and social barriers that could contribute to relapse to high risk behavior. 69 This study, along with another in this issue of the Journal, 70 suggest that though individuals re-entering the community face barriers to successful reintegration, these populations have interest in opportunities that could help them transition, from job training and education to drug treatment programs.…”
Section: Re-entry To the Communitymentioning
confidence: 80%
“…A majority of studies that have attempted to identify barriers to treatment entry and retention have primarily used qualitative methods and life history interviews to explore the nature of perceived barriers (Jessup et al, 2003;Kenny et al, 2011;Notley et al, 2012;van Olphen, Freudenberg, Fortin, & Galea, 2006;Redko, Rapp, & Carlson, 2006;Richie, 2001;Roberts & Nishimoto, 2006). Some have used interviewer administered surveys, or a self-administered questionnaire along with qualitative interviews (Masson et al, 2013;Venner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Studies which have used quantitative methods have generally involved persons seeking outpatient treatment Rinker et al, 2009;Xu et al, 2007) or those who are not help-seeking but have an identified disorder and would be appropriate for treatment, either because of their history (K. E. Green, 2011;Kenny et al, 2011) or a diagnosed substance use disorder (Mojtabi et al, 2011). Few studies (van Olphen et al, 2006;Richie, 2001) have explored barriers to treatment for substance use disorders of men or women returning from jail.…”
Section: Discussionmentioning
confidence: 99%